Global perspectives on the contribution of B cells to multiple sclerosis: an in-depth examination and evaluation - Jiang, Xinzhan; Zhang, Hongyu; Liu, Yongtao (Frontiers in Immunology, 2024)
BackgroundMultiple sclerosis (MS) is a chronic, progressive autoimmune disease, with increasing attention on the role of B cells in its pathogenesis. Despite this growing interest, a comprehensive analysis of research trends and emerging foci on B cells in MS is currently lacking. In this research, we utilize a bibliometric approach to visualize and analyze research trends and focal points in this field, offering a valuable reference for future mechanistic studies in MS.MethodsWe retrieved bibliometric data from the Web of Science Core Collection (WOSCC) for articles published between 2014 and 2023. VOSviewer 1.6.18 and CiteSpace 5.7R3 were used for co-authorship, co-occurrence, and citation analyses to identify key researchers, institutions, countries, and emerging themes in B cell research related to MS.ResultsThe analysis examined 5,578 articles published in 1,041 journals by 5,337 institutions globally. The United States leads in publication output, with Amit Bar-Or identified as the most influential author, and Frontiers in Immunology as the top journal in the field. Research has increasingly focused on the complex role of B cells in MS, particularly their involvement in the central nervous system (CNS) and mechanisms of anti-B cell therapy. Recent trends point to a growing focus on meningeal inflammation, kinase inhibitors, and Epstein-Barr virus, signaling a shift in research priorities.ConclusionThis bibliometric analysis highlights pivotal research trends, key contributors, and emerging areas of interest in B cell research in MS from 2013 to 2024. The findings underscore the growing recognition of the multifaceted role of B cells in MS pathogenesis, particularly their involvement in the CNS compartment and the potential of targeted therapies. The study identifies meningeal inflammation, Epstein-Barr virus infection, and kinase inhibitors as promising avenues for future research. The analyses driving the in-depth exploration of B cell mechanisms in MS and the development of novel diagnostic and therapeutic strategies provide researchers in the MS field with a comprehensive and objective perspective, serving as a valuable reference for accelerating the translation of basic research findings into clinical applications.